Pengaruh Model Discovery Learning Terhadap Hasil Belajar Pendidikan Agama Islam Siswa - Pahmi, Alwan Sadni; Albina, Meyniar (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The purpose of this research is to investigate whether or not the discovery learning model improves students' knowledge of Islamic religious education while they are enrolled in class X at SMA Negeri 3 Kutacane. Experimental quantitative research is used in this study, and the research method that is utilized is a quasi-experimental design. Class X IPA 1 will serve as the experimental class, while class X IPA 2 will play the role of the control class in this research design. Both a Pre-test and a Post-test are included in the testing procedure for the research. On the basis of the findings of the research, a reliability value of 0.550 exceeded the r-table threshold of 0.05. When the sig value for testing the hypothesis is acquired and it is found to be 0.001 more than 0.005, the hypothesis H0 is found to be false. It is possible to draw the conclusion that there is a substantial gap between the learning outcomes attained by students in the experimental class who utilized the discovery learning model and those of students in the control class who utilized the traditional learning model.